Hubungan Antara Job demands Dengan Workplace Well-being Pada Pekerja Shift - Wanda Irawan Anwarsyah; Alice Salendu; Tulus Budi Sulistyo Radikun (Universitas Muria Kudus, 2012)
This study focused on the relationship between job demands withworkplace well-being on shift workers in a company engaged inmanufacturing plastic packaging production. Previous research has not much to explain the relationship between two variables, especially in Indonesia, and its application in shift workers. Workplace well-being is defined as a sense of prosperity gained workers from their jobs, as measured through the Workplace Well-being Index (WWBI) (Page, 2005). Job demands, which is explained by the type of quantitative demands in this study, is defined as something that relates directly to the amount of work to be done and a major source of stress (Kristensen, Bjorner, Christensen, and Borg, 2004), as measured by quantitative questionnaires job demands in the Indonesian Quality of Work Life Questionnaire (IQWiQ) (Radikun, 2010). The sample in this study included 155 shift workers using accidentalsampling. The analysis showed that there was a Significant negative relationship between job demands with workplace well-being on shift workers (r = -0221, p smaller than 0.05, one-tailed). From the research, companies are advised to review the current number of workers with production targets that must be produced, an appreciation ofthe performance of workers and wages.